Informalizing the Formal : Labor Relations in Cambodia - Adler, Daniel (World Bank, Washington, DC, 2018)
The Cambodian labor law of 1997 provides a detailed framework for the regulation of most private sector employment. It provides a framework for industrial relations, including the inclusion of the right for workers to form and be members of unions; the elaboration of the right to bargain collectively; procedures to protect the right to strike; and the establishment of a formal system for the resolution of labor disputes. The case study presented looking at labor reforms in Cambodia highlights innovative ways in which the normative potential of law can be harnessed without relying on formal enforcement mechanisms. Further, it argues that providing support for collective contests and whatever institutional spaces allow such contests to be played out most equitably in a given political moment should be at the forefront of our thinking as law and development practitioners.